2023
DOI: 10.1021/acs.nanolett.3c02247
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Sieving of Ions Using Graphene Oxide: Swelling Peculiarities in Free-Standing and Confined States

Andrei A. Eliseev,
Konstantin E. Gurianov,
Andrei. A. Poyarkov
et al.

Abstract: The paper describes a comparative study of swelling processes in free-standing graphene oxide (GO) membranes and GO laminates encapsulated with epoxy glue. For free-standing graphene oxide membranes, a huge variation in d-spacing in the range of 8–12 Å depending on the ambient humidity and from 12 to >30 Å depending on the electrolyte type and its concentration was revealed using direct in situ and in operando XRD studies. Limited swelling at various humidity levels as well as in electrolyte solution with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The interlayer spacing plays an important role in the transport properties of GO. The unique interlayer expansion of GO opens up opportunities for accurate control of functional properties such as tunable ionic transport through GO membranes for water purification and desalination. , The rapid responses of ordered GO layer structures can be utilized in ultrafast humidity sensors. ,, However, the swelling can also have an adverse effect on certain applications. For example, it has been found that the water purification performance of a GO membrane is far below its ideal performance due to the swelling effect of GO in aqueous solutions …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interlayer spacing plays an important role in the transport properties of GO. The unique interlayer expansion of GO opens up opportunities for accurate control of functional properties such as tunable ionic transport through GO membranes for water purification and desalination. , The rapid responses of ordered GO layer structures can be utilized in ultrafast humidity sensors. ,, However, the swelling can also have an adverse effect on certain applications. For example, it has been found that the water purification performance of a GO membrane is far below its ideal performance due to the swelling effect of GO in aqueous solutions …”
Section: Introductionmentioning
confidence: 99%
“…The swelling behavior of GO is typically studied by measuring the change in d -spacing by X-ray diffraction (XRD). ,,, However, the disruption of the interlayer periodicity by swelling results in substantial peak broadening in diffraction spectra . In addition, XRD scans typically take at least a few minutes and are not easily obtained in controlled environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation